Comparing Warm Compress and Effleurage Massage to Reduce Back Pain in Third-Trimester Pregnant Women in the Working Area of Maracang Health Center, Purwakarta Regency - Lathifah, Maulida (CV. Publikasi Indonesia, 2025)
Anatomical and hormonal changes cause the appearance of back pain complaints in pregnant women in the third trimester. The prevalence of back pain in Indonesia is 18%. Non-pharmacological methods such as effleurage massage and warm compresses can provide benefits in reducing back pain. This study aims to compare the effectiveness of warm water compresses with effleurage massage in reducing the intensity of back pain in pregnant women in the third trimester within the working area of the Maracang Health Center, Purwakarta Regency. This quantitative research employs a quasi-experimental design with a pre- and post-test two-group approach. The research sample consisted of 32 pregnant women in the third trimester, divided into two groups: the effleurage massage group and the warm compress group, with 16 respondents in each. Pain intensity was measured using the Numeric Rating Scale (NRS). Data were analyzed using an independent samples t-test. The results of the independent samples t-test showed a p-value of 0.444, indicating that there was no significant difference between warm compresses and effleurage massage in reducing the scale of back pain in pregnant women in the third trimester; thus, both warm compresses and effleurage massage are equally effective in reducing back pain in pregnant women in the third trimester.